Điều kiện sinh khí hậu tại một số khu điều dưỡng thuộc vùng núi phía bắc Việt Nam - Vân, Nguyễn Khanh; Hiền, Nguyễn Thị (Vietnam Journal of Earth Sciences, 2001)
Bioclimatic conditions in some sanatorium areas of Northern mountainuos part of Vietnam